2023
DOI: 10.21203/rs.3.rs-2918296/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breast Cancer Awareness and Associated Factors among Students of Allied Health Sciences in Indonesia and Pakistan: A cross-sectional study

Abstract: Background Breast-cancer-related morbidity and mortality has been shown to be decreased by the implementation of worldwide-accepted screening guidelines, and by appropriate education and training of health professionals on risk identification and screening. This study aims to determine the significance of educational sessions in improving health professionals’ knowledge about breast cancer, particularly screening modalities that can optimalise patient outcomes. Methods A cross-sectional survey was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Married students knew more about breast cancer than single or never-married students. This study suggests that being married or in a stable relationship may be associated with higher levels of breast cancer knowledge due to increased social support and access to health information [ 66 ]; furthermore, a study conducted in China reported that breast cancer awareness was associated with having a high level of health information literacy, husbands with higher education levels, etc. [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Married students knew more about breast cancer than single or never-married students. This study suggests that being married or in a stable relationship may be associated with higher levels of breast cancer knowledge due to increased social support and access to health information [ 66 ]; furthermore, a study conducted in China reported that breast cancer awareness was associated with having a high level of health information literacy, husbands with higher education levels, etc. [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with Tayyeb’s study, where younger students in the Allied Health Sciences program scored worse on knowledge, while female students over 50 scored higher. Furthermore, postgraduate students showed more awareness of breast cancer markers and information than undergraduate students [ 66 ].…”
Section: Discussionmentioning
confidence: 99%